2003
DOI: 10.1037/0894-4105.17.3.517
|View full text |Cite
|
Sign up to set email alerts
|

Implicit learning of visuospatial sequences in schizophenia.

Abstract: The authors examined whether patients with schizophrenia learned sequential patterns in a probabilistic serial response time task in which pattern trials alternated with random ones. Patients showed faster and more accurate responses to pattern trials than to random trials, but controls showed greater sensitivity to patterns. The highest level of regularity learned in both groups was information about runs of 3 events. Pattern learning occurred largely outside of awareness, as participants could not describe p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
40
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 79 publications
4
40
1
Order By: Relevance
“…For example, age deficits are most clearly seen in accuracy learning measures (Howard et al 2004a). The same was the case for schizophrenics versus normal controls (Schwartz et al 2003). In addition, the present paradigm may be useful for neuroimaging studies, as concurrent explicit/implicit learning paradigms increasingly have been used to reveal deficits in frontal-striatal recruitment for certain populations such as older adults (Howard et al 2004b;Aizenstein et al 2006).…”
Section: Reaction Time/accuracy Dissociationmentioning
confidence: 80%
See 1 more Smart Citation
“…For example, age deficits are most clearly seen in accuracy learning measures (Howard et al 2004a). The same was the case for schizophrenics versus normal controls (Schwartz et al 2003). In addition, the present paradigm may be useful for neuroimaging studies, as concurrent explicit/implicit learning paradigms increasingly have been used to reveal deficits in frontal-striatal recruitment for certain populations such as older adults (Howard et al 2004b;Aizenstein et al 2006).…”
Section: Reaction Time/accuracy Dissociationmentioning
confidence: 80%
“…Imaging studies have shown that sequence learning depends on frontal-striatal circuits (Barone and Joseph 1989;Rauch et al 1997;Exner et al 2002;Destrebecqz et al 2005;Aizenstein et al 2006;Ashe et al 2006;Histed and Miller 2006), making it useful for the study of disorders such as schizophrenia (Weickert et al 2002;Schwartz et al 2003), OCD (Kathmann et al 2005), Parkinson's disease (Smith and McDowall 2004), mild cognitive impairment (Negash et al 2006), and dyslexia ).…”
mentioning
confidence: 99%
“…Studies to date that have examined SRT-type learning in this population have used visuospatial sequences (Green et al, 1997;Kumari et al, 2002;Schwartz et al, 2003). Schizophrenia patients are known to have problems holding spatial information in mind (Park & Holzman, 1992), shifting attention (Braff, 1993), and directing eye movements (Phillips & David, 1997 ).…”
Section: Introductionmentioning
confidence: 99%
“…Howard & D. Howard, 1997;J. Howard et al, 2004;Negash et al, 2003;Schvaneveldt & Gomez, 1998;Schwartz et al, 2003). Participants were given extensive exposure to the letter sequence over six 1 hr sessions so that patients had sufficient opportunity to learn the sequence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation